Spectrum analysis of seismic acceleration records from Tohoku District of Japan - Trinidad, Ariston G.; Ogawa, Junji; Loo, Yew-Chaye; Ping Kunawatsatit; Government of The Netherlands (Bangkok : Asian Institute of Technology, 1981)
The response spectra of earthquake records from Tohoku District of Japan are analyzed in terms of the displacement, velocity and acceleration response spectra. Observations of spectral behavior considering individual. stations recording different earthquakes, groups of stations having different site characteristics and stations with the same base rock movement are explained with reference to local soil conditions. Various parameters which influence the response spectra are minimized by normalization or by proper choice of earthquake records. It is found that the response spectra of earthquake motions are related to the depth and nature of soil deposits underlying the recording stations.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Spectrum analysis; Earthquake intensity